Mental Illness and Opioid Epidemic in the United States - Evelio Velis; Selene Borras; Sumera Khaja (European Scientific Journal, ESJ, 2018)
Introduction: According to the World Health Organization (WHO), mental health is defined as a state of well-being in which every individual realizes his or her own potential, can cope with the normal stresses of life, can work productively and fruitfully, and is able to make a contribution to her or his community. A drug overdose is defined, by the Medical Dictionary, as the accidental or intentional use of a drug or medicine in an amount that is higher than is normally used. Accidental drug overdose may be the result of misuse of prescription medicines or commonly used medications like pain relievers and cold remedies. Overdose with opiate drugs causes sedation, low blood pressure, slowed heart rate, and slowed breathing. A serious risk is that the patient will stop breathing. Methods: A multiple correlational analysis was conducted to explore the potential strength, direction and significant of relationship between selected indicators related to mental illness, socioeconomic factors and drug related deaths in the United States, at the state level. A level of significance of 0.05 was selected for all tests of significance. Conclusion: There is a strong and significant correlation at the state level between the mental illness, major depressive disorders, drug use/abuse and drug overdose related deaths. Veterans living in the state and un-insured individuals are significantly correlated with drug overdose related deaths. No significant correlation was identified between socio-economic factors typically associated with most health issues such as poverty and the current opioid epidemic affecting our nation.